Evaluasi Faktor Penghambat Proses Pengadaan Barang/Jasa Melalui E-Procurement (Studi Pada Sekretariat Jenderal KESDM) - ANGGORO, RENALDI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Today, public goods and service procurement become an important rumor to fulfill the society needs. Goods and service procurement through electronic (e-procurement) in the government unit as an answer for society demands to fulfill efficiency, transparency and accountability procurement. The aim from this research is to evaluate the factor that hampers e-procurement in secretary general Ministry of energy and mineral resources. This kind of research is qualitative descriptive using study case. Data from this research submit through interview and observation from the people that have contribution in goods and service procurement. Data evaluated by using the technique analysis data qualitative research by Miles and Huberman (1992) to combination the data that we get from the respondent. From the evaluation, the factor that hampers e-procurement has fulfill five components internal controls that known as COSO. But control risk need more attention from government the reason are, need to improve the technical skill from the staff and also from the company, and optimally the transparency and accountability and increase the prudent to process the goods and public service